Does knowledge of fetal outcome influence the interpretation of intrapartum cardiotocography and subsequent clinical management?: A multicentre European study - Reif, Philipp; Schott, Sarah (BJOG, 2016)
Objective To investigate whether knowledge of fetal outcome influences retrospective interpretation of cardiotocographic tracings and subsequent management recommendations. Design Prospective online study. Setting Seven university hospitals in five European countries. Population Forty-two intrapartum tracings from women with singleton pregnancies and uneventful antepartum courses. Methods Using an online questionnaire, 123 healthcare professionals interpreted 42 tracings without any knowledge of fetal outcome and provided management recommendations according to the National Institute of Clinical Excellence guidelines (intrapartum care). Two months later, 93 of the 123 participants re-interpreted the same re-ordered tracings, this time with information on the newborn's umbilical artery pH. Outcome measures Comparison of the evaluation of tracing features, overall tracing classification, and management recommendations between the initial analysis and re-interpretation. Results In newborns with umbilical artery pH ≤ 7.05, knowledge of the pH value led to significant changes in the evaluation of all basic tracing features. In this group, classification of tracings as ‘normal’ decreased 76% (8.8-2.1%, P < 0.001), whereas classification as ‘pathologic’ increased 51% (44.7-67.5%, P < 0.001). In newborns with pH 7.06-7.19, classification of tracings as ‘normal’ decreased 36% (22.4-14.4%, P < 0.001), and in those with pH ≥ 7.20, classification of tracings as ‘pathologic’ decreased 40% (23.4-14.1%, P < 0.001). In the group of newborns with umbilical artery pH ≤ 7.05, the recommendations ‘no attention needed’ decreased 75% (10.2-2.6%, P < 0.001), and the number of recommendations ‘rapid reversal of hypoxic cause or immediate delivery’ increased 70.3% (42.1-71.7%, P < 0.001). Conclusions When provided with information on adverse fetal outcome, healthcare professionals provide a more pessimistic evaluation of basic tracing features, overall classification, and clinical management recommendations. Tweetable abstract Knowledge of adverse fetal outcome leads to more pessimistic CTG evaluation and management recommendations.